Technology Adoption and E-Learning in Higher Education: An Analysis by using Meta Analyses (Global Journal of Human-Social Science, 2019)
The increase use of new technology has made a huge change in higher education Use of new electronic tools as computer internet audio video conferences likewise which are helpful in learning higher education This study aims to analyze the attitude of students teachers and administrators towards technology adoption and e learning in higher education To accomplish the objective it examines the ten previous research studies based on the e learning and new technology adoption in higher education In this study meta analyses has used as a statistical tool to analyze the study and recorded that the acceptance of the null hypothesis This study found that the students teachers and administrators are positively accepted the technology adoption and e learning in higher education The teachers and students has increased their use of new technology while delivering their lectures make their assignments presenting their views in seminars conferences and workshops
Keywords: meta analyses; e- learning; technology; adoption; attitude; information and communication technologies